Penerapan Digital Government di Desa Sukajaya Kabupaten Sumedang Jawa Barat - Ami Afriyani; Idah Wahidah; Muhammad Taufiq Hatta Wibowo (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
The presence of the use of information and communication technology in government as a digital-government concept, is aim at helping the government optimize performance in providing services effectively and efficiently. One way for the government to take advantage of new technology is to provide the public with easier access to government information and services and to improve the quality of services provided. The purpose of this study is to describe the application of digital in public services in Sukajaya Village, Sumedang Regency, West Java Province as an effort to improve the quality of public services in the 4.0 era. This research method uses a qualitative descriptive approach, with data collection and techniques used are observation, direct interviews, and literature studies sourced from many articles in journals, books, relevant regulations, information media content related to the focus, and research problems. The results of the study indicate that the application of digital in Sukajaya Village is still in the cataloging stage, where this stage is the digital government process as a one-way communication relationship between the community and the government. In this stage, all forms of announcement information are posted in digital form. This research article concludes that Sukajaya Village in implementing digital government pays attention to government readiness factors, including resource readiness, IT readiness, cognitive readiness, innovation readiness, partnership readiness, cultural readiness, and structural readiness.